(untitled) (Community Based Medical Journal, 2025)
A cross-sectional, descriptive study was done in the Department of Anatomy, of Mymensingh Medical College, Mymensingh, Bangladesh, from January to December of 2023, to measure the neck circumference of the dry human fibula in an adult Bangladeshi population. This study was done using 300 dry human fibula (right siders 152 and left sided 148) samples, which were selected through purposive sampling technique. Any damaged, unossified, fractured fibula were excluded in this study. Data was collected, scrutinized and compiled, then analyzed using Microsoft Excel. Data was presented through histogram. The mean neck circumference of the right sided fibulae was 3.4±0.50 cm. The neck circumference of 152 right sided fibulae ranged between 2.5 cm and 5 cm. The mean neck circumference of the left sided fibulae 3.59±0.55 cm. The neck circumference of 148 left sided fibulae ranged between 2 cm and 5 cm. Our data is expected to enrich the information pool for the general physicians, orthopaedic surgeons, forensic specialists and anthropologists to improve their knowledge and understanding regarding various anatomical parameters of human fibula. CBMJ 2025 July: vol. 14 no. 02 P:146-148